Rituximab maintenance for the treatment of patients with follicular lymphoma: an updated systematic review and meta-analysis of randomized trials - Vidal, Liat; Gafter-Gvili, Anat; Salles, Gilles; Dreyling, Martin H.; Ghielmini, Michele; Hsu Schmitz, Shu-Fang; Pettengell, Ruth; Witzens-Harig, Mathias; Shpilberg, Ofer (Journal of the National Cancer Institute, 2011)
In a previous systematic review and meta-analysis of five randomized controlled trials comparing rituximab maintenance with no maintenance (observation or rituximab at progression) for patients with follicular lymphoma, we reported that rituximab maintenance treatment improved the overall survival of patients. In this study, we did a similar search of the electronic databases updated through December 31, 2010, and included nine trials and 2586 follicular lymphoma patients. Hazard ratios (HRs) for time-to-event data were estimated and pooled using the inverse variance method. Risk ratios for dichotomous data were pooled using a fixed effect model. Patients treated with rituximab maintenance had improved overall survival (pooled HR of death = 0.76, 95% confidence interval [CI] = 0.62 to 0.92) compared with patients in the no maintenance group. Patients with refractory or relapsed (ie, previously treated) follicular lymphoma treated with rituximab maintenance had improved overall survival (pooled HR of death = 0.72, 95% CI = 0.57 to 0.91), whereas previously untreated patients had no survival benefit (pooled HR of death = 0.86, 95% CI = 0.60 to 1.25). The rate of infection-related adverse events was higher in the rituximab maintenance group (pooled risk ratio = 1.67, 95% CI = 1.40 to 2.00). These results further support the use of rituximab maintenance in the standard of care for refractory or relapsed follicular lymphoma.
Gesehen am 08.12.2022